Some Unsettled Issues in a Second Phase of the Cambridge-Cambridge Controversy - Lazzarini, Andrés Lucas Rodrigo (2015)
The aim of this paper is to clear up some issues in a second phase of the Cambridge-Cambridge capital theory controversies, when the neoclassical argument was chiefly conducted in terms of the Walrasian specification of capital in intertemporal and temporary general equilibrium models. It is held that the response by the neoclassical side in that phase has not been as satisfactory to rebut the implications of reswitching and capital reversing as some neoclassical scholars have argued. The reason for this can be traced in the overlooking of the implications of the redefinition of equilibrium implied in those models.